Penatalaksanaan Holistik Pada Anak Dengan Skabies Melalui Pendekatan Kedokteran Keluarga Di Puskesmas Rawat Inap Gedong Tataan - Katya Rizqita Fitriana; Joana Sirooj Irsyaadyah; Aila Karyus (Medula, 2022)
Scabies is a skin disease caused by infestation and sensitization of the parasite Sarcoptes scabiei var. hominist. According to the World Health Organization (WHO), scabies often occurs in tropical and hot countries and in areas with high population density. It is also estimated that there are 200 million people worldwide suffer from scabies at one time and an estimated 10% of children in poor areas. Risk factors for scabies include socio-economic and low knowledge, personal hygiene and poor environment. Scabies is often overlooked because it is not life threatening. Appropriate case management holistically using a family medicine approach is needed to achieve therapeutic success and break the chain of disease transmission to the community. Patient An. AK aged 18 months came with complaints of itching since 2 months ago and there were small nodules the size of a pin filled with clear fluid in the itchy area which were then scratched and broke. Complaints have not been treated, and the longer the itching gets worse. The patient is worried that the complaint getting worse, not disappear and not heal so that it interferes with the patient's activities. Clinically the patient was diagnosed with scabies (ICD-10 B.86; ICPC-2:S72). Internal risks in the form of lack of personal and environmental hygiene, lack of knowledge, inappropriate treatment behavior. External risks include friends and family members who have the same complaint, lack of family hygiene, lack of family knowledge. Functional grade 1, which is able to carry out activities as before the illness without difficulty. Furthermore, holistic management is carried out, namely intervention using poster media. In the evaluation, the results obtained in the form of a better understanding of the disease and changes in behavior that have an impact on the success of therapy.